Carboxylesterase genes in nitenpyram‐resistant brown planthoppers, Nilaparvata lugens. (20th July 2020) - Mao, Kaikai; Ren, Zhijie; Li, Wenhao; Cai, Tingwei; Qin, Xueying; Wan, Hu; Jin, Byung Rae; He, Shun; Li, Jianhong
Abstract: Carboxylesterases (CarEs) represent one of the major detoxification enzyme families involved in insecticide resistance. However, the function of specific CarE genes in insecticide resistance is still unclear in the insect Nilaparvata lugens (Stål), a notorious rice crop pest in Asia. In this study, a total of 29 putative CarE genes in N. lugens were identified, and they were divided into seven clades; further, the β ‐esterase clade was significantly expanded. Tissue‐specific expression analysis found that 17 CarE genes were abundantly distributed in the midgut and fat body, while 12 CarE genes were highly expressed in the head. The expression of most CarE genes was significantly induced in response to the challenge of nitenpyram, triflumezopyrim, chlorpyrifos, isoprocarb and etofenprox. Among these, the expression levels of NlCarE2, NlCarE4, NlCarE9, NlCarE17 and NlCarE24 were increased by each insecticide. Real‐time quantitative polymerase chain reaction and RNA interference assays revealed the NlCarE1 gene to be a candidate gene mainly involved in nitenpyram resistance, while simultaneously silencing NlCarE1 and NlCarE19 produced a stronger effect than silencing either one individually, suggesting a cooperative relationship in resistance formation. These findings lay the foundation for further clarification of insecticide resistance mediated by CarE in N. lugens .